Hydrogen-EGR synergy as a promising pathway to meet the PM–NOx–BSFC trade-off contingencies of the diesel engine: A comprehensive review. (5th October 2015) - Banerjee, Rahul; Roy, Sumit; Bose, Probir Kumar
Abstract: The present study attempts to provide an illustrative overview of hydrogen dual fuel applications in existing diesel engine configurations to distinctly outline the tactical and strategic pertinence of hydrogen in meeting the impeding challenges of the diesel engines of the day. To this end, a comprehensive review of the challenges and opportunities of contemporary diesel engine operation and the unique relevance and beneficence of hydrogen in diesel operational paradigms have been established through unique Strength-Weakness-Opportunity-Threat analyses. The survey also outlines the exceptional tolerance of hydrogen combustion towards higher exhaust gas recirculation rates than that deemed feasible in diesel engine paradigms of the day to meet its emission obligations. The present review establishes through various case studies, the possibility of continuing with exhaust gas recirculation as a cost-effective and simple pathway of NOx containment strategy in conventional diesel combustion domains in lieu of the costly and yet to mature exhaust after treatment systems. The study in its entirety attempts to establish the synergistic potential of hydrogen-exhaust gas recirculation technique as a viable, ready-to-be-adapted in-situ strategy that can be exploited in existing diesel powertrains to meet its present and impending PM–NOx –BSFC trade-off challenges. Highlights: The omnipresent diesel PM–NOx –BSFC trade-off paradox. Increasingly strict diesel PM–NOx emission mandates. Diesel after treatment systems yet to mature as a viable solution. LTC concepts not yet scalable to all regimes of diesel engine operation. H2 -EGR synergy provides a strategic pathway to the diesel trade-off problem.